Making the Poor Count Takes More than Counting the Poor: A Quick Poverty Assessment of the State of Bahia, Brazil - Verner, Dorte (World Bank, Washington, D.C., 2013)
The state of Bahia, Brazil has made progress in reducing poverty and improving social indicators in the past decade. Despite this progress, Bahia's poverty is among the highest and its social indicators are among the lowest in Brazil. Currently, 41 percent of Bahia's population live in households below the poverty level, a drop of 14 percentage points since 1993. Moreover, poverty is less deep than in 1993, but deeper than in 1981. The fall in Bahia's social indicators, such as infant mortality and adult illiteracy, corroborate the improvement in measured income poverty. Part of the reason why the poverty indicators of Bahia are worse than in other countries with similar per-capita income is because of income inequality. In 2000 the Gini coefficient for Bahia was 0.61. The National Household Survey Data, PNAD, from 1981-2001 reveal that living in Bahia does not by itself affect the probability of falling below the poverty line in Brazil. Hence, other characteristics are more important for poverty reduction than geographical location. The strongest poverty correlates are education, experience, race, rural location, gender, and labor market association. Analyses reveal that the probability of being poor is decreasing with increasing educational attainment. The gender of the household head does not matter for poverty according to the poverty profile, but when we control for education and other individual characteristics, female-headed households have a much larger likelihood of being poor than do male-headed households. Household size also matters for poverty. Larger households are more likely to experience poverty than smaller households, and the effect is concave. Moreover, households with members under age five appear more likely to fall below the poverty line than families with no children below five years old. The presence of old-aged people (above 65 years of age) in the household is an important factor contributing to poverty reduction.